2017
DOI: 10.21608/scumj.2017.46085
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Oral Squamous Cell Carcinoma using Thymoquinone Loaded on Gold Nanoparticles

Abstract: Background: Oral cancer is one of the most prevalent cancers. Thymoquinone has a potential therapeutic activity against cancer cells. Aim: to compare the effect of thymoquinone and thymoquinone loaded on gold nanoparticles (GNPs-TQ) as systemic therapeutic agents through intraperitoneal injection for 3&6 weeks after painting of with DMBA 3 times/week for 14w. Material and Methods: This study was carried out on ninety male Syrian golden hamsters (n=90), its age ranged from 6 to 7 weeks, weighting 90-110 gm, pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 13 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…after DMBA. (38) The best results from both studies were obtained with 0.001 mg/kg TQ loaded on GNps.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…after DMBA. (38) The best results from both studies were obtained with 0.001 mg/kg TQ loaded on GNps.…”
Section: Discussionmentioning
confidence: 94%
“…Similar results were obtained from this combination in previous studies carried out in the same model. (35,38) These studies reported inactivation of the Nf-κB protein, in the groups treated with TQ, or TQ-GNps (in different concentrations), whether used topically, 35 or given i.p. after DMBA.…”
Section: Discussionmentioning
confidence: 99%
“…after DMBA. 15 The best results from both studies were obtained with 0.001 mg/kg TQ loaded on AuNps. Group D2 (0.001 mg/kg TQ loaded on GNps for 12 weeks) in the present study, showed IHC intense stain (score 3) along with the epithelial layers.…”
Section: Discussionmentioning
confidence: 94%
“…Similar results were obtained from this combination in previous studies carried out in the same model. 15,21 These studies reported inactivation of the Nf-κB protein, in the groups treated with TQ, or AuNps-TQ (in different concentrations), whether used topically, [21] or given i.p. after DMBA.…”
Section: Discussionmentioning
confidence: 99%
“…It was used to study the carcinogenesis process, prevention and treatment of oral cancer. (2)(3)(4) Dimethylbenza-a-anthracene (DMBA) is one of the polycyclic hydrocarbons (PAHs), which are environmental carcinogens as products of incomplete fuel combustion (in air), water, soil, food supply, cigarette smoke and alcohol. (5,6) When DMBA is painted to the hamster buccal pouch (HBP) for 6 weeks (0.5% in mineral oil, 3/week) it results in epithelial dysplasia, (3) while for 12-14 weeks it results in invasive well differentiated squamous cell carcinoma (SCC).…”
Section: Introductionmentioning
confidence: 99%